越南語右緣助詞không的左緣本質 - 廖苡伶(Y.-L. Irene Liao); 林宗宏(T.-H. Jonah Lin) (Taiwan Journal of Linguistics, 2024)
This work provides a syntactic account of VP-không questions in Vietnamese. We begin by pointing out potential problems in Duffield's (2013a) predicate-raising analysis to VP-không questions. First, it is unclear why raising the predicate to the left of the negator không could turn a declarative into a question. Second, Duffield's analysis cannot account for the occurrence of TP-level adverbs between the subject and the predicate. Third, contrary to a claim in Duffield's analysis, the topic marker thì is actually compatible with VP không questions. To deal with these problems, we argue for an alternative analysis which involves Neg-to-C movement and the raising of a remnant TP.